Grammar rules for reading comprehension for 6th grade primary school students in the communication department. IE Fe y Alegría N° 12. Puente Piedra - Coveñas Prado, Edith Juliana (2025)
Grammar rules, in general terms, are the set of rules used by any language to establish the guidelines to ensure the message is understood by the recipient. Communication is based on comprehension, and therefore, without a series of patterns that define a course of action, it would be impossible to establish fluid and correct communication between the two parties. Therefore, it is important to determine whether Grammar Rules influence reading comprehension in sixth-grade elementary school students at Fe y Alegría N. 12 Elementary School in Puente Piedra, Lima. Quantitative approaches, using a hypothetical-deductive method and a quasi-experimental design, frame the research methodology. A control group and an experimental pre- and post-test group constitute the intentional non-probability sample. It was concluded that teaching skills using Grammar Rules increased reading comprehension at the critical level by finding sig (002) in the experimental group post-test. Therefore, there was a significant effect of the teaching strategies used.